2017
DOI: 10.1016/j.jare.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Novel angiotensin-converting enzyme inhibitory peptides from caseins and whey proteins of goat milk

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(87 citation statements)
references
References 29 publications
1
78
0
8
Order By: Relevance
“…Thus, the ACE-inhibitory effect of peptides depend on the presence of hydrophobic and aromatic amino acid residues at one or more C-terminal position of peptides and/or N terminal branched aliphatic amino acids side-chains residues (35, 43). Potent ACE-inhibitory peptides were mostly characterized by the presence of Phe, Tyr, and Tryp and Pro at one or more C-terminal positions (35, 44).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the ACE-inhibitory effect of peptides depend on the presence of hydrophobic and aromatic amino acid residues at one or more C-terminal position of peptides and/or N terminal branched aliphatic amino acids side-chains residues (35, 43). Potent ACE-inhibitory peptides were mostly characterized by the presence of Phe, Tyr, and Tryp and Pro at one or more C-terminal positions (35, 44).…”
Section: Resultsmentioning
confidence: 99%
“…Other minerals such as magnesium and potassium may also help regulate blood pressure, but their individual contributions are not easy to detect when present in calcium-rich foods (Xu et al, 2008). The most important effect could be attributed to bioactive peptide like casein, whose inhibitory effect on the angiotensin-1 converting enzyme has already been demonstrated in the process of controlling blood pressure (Rousseau-Ralliard et al, 2010;Ibrahim et al, 2017). Other studies have revealed that certain milk peptide derivatives also have hypotensive effects via endothelin 1 modulation, performed by the endothelial cell (German et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular health: Hypertension and hyper cholesterolemic have become major cardiovascular problems in elderly men and women all over the world. Whey proteins alpha-lactoalbumin, beta-lactoglobulin have exhibited angiotensin converting enzyme (ACE) inhibitory peptides (Ibrahim et al, 2017;Patil et al, 2015;Tavares et al, 2011) and antithrombotic activity as well as cholesterol reducing activity (Li et al, 2003). Angiotensin converting enzyme (ACE) is known to change inactive proteins into proteins that constrict blood vessels and thus increase the blood pressure.…”
Section: Composition Of Wpcmentioning
confidence: 99%